Comparison Ghrehlin at Obesity Without Metabolic Sydrome With Obesity with Metabolic Syndrome - Rusdiana; Savira, Maya; Widjaja, Sry Suryani (Talenta Publisher, 2021)
Obesity is principal causative factor in the development of metabolic syndrome and Ghrelin as human natural hormones is involved in fundamental regulatory processof eating and energy balance.Obesity, which has become a global public health problem, is one of the major risk factors for development metabolic syndrome and type 2 diabetes mellitus.This study aimed to analyze the comparison of ghrelin hormone levels in obese with metabolic syndrome and obese non metabolic syndrome . The sample population is obese adults, then we examined the weight, height, waist size, blood pressure, laboratory tests such as blood sugar levels and lipid profile of sample population to separate obese with metabolic syndrome and obese non metabolic syndrome. After we determined each group we measured stress oxidative levels in blood in obese with metabolic syndrome and obese non metabolic syndrome by ELISA method.With statistical analysis using T test found that there was significant difference of ghrelin hormone levels between obese with metabolic syndrome and obese without metabolic syndrome (p<0.005).